2019
DOI: 10.1177/1940082919869487
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Endangered Mekong Giant Catfish, Striped Catfish, and Their Hybrids From Thailand

Abstract: Previous genetic investigations of the Mekong giant catfish ( Pangasianodon gigas Chevey, 1913) and striped catfish ( Pangasianodon hypophthalmus Sauvage, 1878) provided discordant results. Here, we sequenced mitochondrial (mt) DNA of the cytochrome B region, and a control region, to characterize the genetic variation of P. gigas, P. hypophthalmus, and hybrids of these two species. Among the three groups, P. hypophthalmus had the greatest diversity in both regions, yet all three studied groups showed lower gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…mekongensis could be divided into four groups based on the mitochondrial cytb gene. This result was consistent with reports of fish populations that examined genetic variation during succession by using the cytb gene [ 14 , 15 , 36 ]. In Oryzias , Takehana et al [ 16 ] reported the use of the cytb gene to understand the diversity of wild Japanese medaka populations that correlated with their geographic variation in Japan.…”
Section: Discussionsupporting
confidence: 92%
“…mekongensis could be divided into four groups based on the mitochondrial cytb gene. This result was consistent with reports of fish populations that examined genetic variation during succession by using the cytb gene [ 14 , 15 , 36 ]. In Oryzias , Takehana et al [ 16 ] reported the use of the cytb gene to understand the diversity of wild Japanese medaka populations that correlated with their geographic variation in Japan.…”
Section: Discussionsupporting
confidence: 92%
“…Conservation can be supported using genetic variation, especially concerning population health. Populations and genetic uniformity in populations causes conservation of population vulnerability (Phadphon et al 2019). The genetic variation of the Limboto Lake population has an Hd value above 0.5 and a Pi value below 0.005, so the Limboto Lake population can be grouped as having high Hd and low Pi.…”
Section: Discussionmentioning
confidence: 99%